2022
DOI: 10.18087/cardio.2022.1.n1859
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and echocardiographic parameters of patients with COVID-19 pneumonia three months and one year after discharge

Abstract: Aim    To study changes in clinical and echocardiographic parameters in patients after documented COVID-19 pneumonia at 3 months and one year following discharge from the hospital. Material and methods    The study included 116 patients who have had documented COVID-19 pneumonia. Patients underwent a comprehensive clinical evaluation at 3 months ± 2 weeks (visit 1) and at one year ± 3 weeks after discharge from the hospital (visit 2). Mean age of the patients was 49.0±14.4 years (from 19 to 84 years); 49.6 % w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…В свою очередь ремоделирование миокарда на фоне АГ является серьезным предиктором смертности от ССЗ [17]. Существуют данные, что у реконвалесцентов инфекции COVID-19 наблюдается увеличение внешней и внутренней площади МЛЖ и ММЛЖ, что ведет к увеличению частоты ССЗ [18]. Согласно полученным нами данным, ИММЛЖ в пересчете на рост у пациентов Т а б л и ц а 2…”
Section: Discussionunclassified
“…В свою очередь ремоделирование миокарда на фоне АГ является серьезным предиктором смертности от ССЗ [17]. Существуют данные, что у реконвалесцентов инфекции COVID-19 наблюдается увеличение внешней и внутренней площади МЛЖ и ММЛЖ, что ведет к увеличению частоты ССЗ [18]. Согласно полученным нами данным, ИММЛЖ в пересчете на рост у пациентов Т а б л и ц а 2…”
Section: Discussionunclassified
“…Compared to three months post-discharge, a higher prevalence of cardiovascular diseases was observed one year after recovery, which is driven primarily by the development of arterial hypertension and chronic heart failure. Echocardiography reveals changes in ventricular geometry accompanied by a decline in diastolic and systolic function of the left ventricle (LV), including reduced global longitudinal strain and deformation in the apical myocardium and partially the mid myocardial segments [108]. In the long term, patients recovered from the COVID-pneumonia can develop alterations in the right heart chambers.…”
Section: Post-covid Syndromementioning
confidence: 99%
“…[4][5][6][7][8] In our previous study on this topic, we found an incidence of aPH, based on echocardiographic criteria, of 39% in Covid-19 patients admitted to intensive care (ICU) and that early mortality (21 days) was increased more than 6-fold compared to patients without signs of aPH. 4 In previous follow-up reports on hospitalized Covid-19 patients, 9,10 the issue of aPH has not been reported in any detail.…”
Section: Introductionmentioning
confidence: 99%
“…In previous follow‐up reports on hospitalized Covid‐19 patients, 9,10 the issue of aPH has not been reported in any detail. Against the results of our previous study, we hypothesized that mortality may continue to be elevated after 1 month in patients with Covid‐19 and aPH.…”
Section: Introductionmentioning
confidence: 99%